Dual-carrier processing to convey temporal fine structure cues: Implications for cochlear implants - Apoux, Frédéric (J Acoust Soc Am, 2015)
Speech intelligibility in noise can be degraded by using vocoder processing to alter the temporal fine structure (TFS). Here it is argued that this degradation is not attributable to the loss of speech information potentially present in the TFS. Instead it is proposed that the degradation results from the loss of sound-source segregation information when two or more carriers (i.e., TFS) are substituted with only one as a consequence of vocoder processing. To demonstrate this segregation role, vocoder processing involving two carriers, one for the target and one for the background, was implemented. Because this approach does not preserve the speech TFS, it may be assumed that any improvement in intelligibility can only be a consequence of the preserved carrier duality and associated segregation cues. Three experiments were conducted using this “dual-carrier” approach. All experiments showed substantial sentence intelligibility in noise improvements compared to traditional single-carrier conditions. In several conditions, the improvement was so substantial that intelligibility approximated that for unprocessed speech in noise. A foreseeable and potentially promising implication for the dual-carrier approach involves implementation into cochlear implant speech processors, where it may provide the TFS cues necessary to segregate speech from noise.